Literature and Political Economy: An Invitation - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2019)
Most people think of science and literature as distinct human endeavours. According to received convention, science is mostly about 'mind', whereas literature is largely about 'heart'. Science, goes the argument, is by and large rational, literature primarily emotional. Science is about thinking, literature about feeling. The practical implication of this duality is that many who consider themselves scientists - particularly in the so-called 'social sciences' and especially in 'economics' - pay little or no attention to belles-lettres. As far as they are concerned, fiction, poetry and drama are diversions from serious academic work. Occasionally, when going on vacation or to an academic conference, they'll throw a few cheap thrills into their handbag for 'relaxation'. They'll use them instead of sleeping pills after they are done surfing their phones and zapping their telescreen's channels. Now, it is true the that line between creative belles-lettres and capitalized cheap thrills has blurred in recent decades - so much so that it's sometimes difficult to tell them apart. And it is also true that as the number of new novels exploded, their average quality plummeted. But these shifting patterns are secondary. There is no need to read Leon Trotsky's path-breaking book on Literature and Revolution (1925) or C.P. Snow's warning on The Two Cultures and the Scientific Revolution (1959) to realize that literature in general and novels in particular remain crucial for understanding - and occasionally affecting - the socio-scientific history of humanity.
Keywords: P16; Z1; 330; bisociation; literature; political economy